Omalizumab as an adjuvant therapy for treating severe atopic dermatitis in children. A serie of cases - María García (Revista Alergia México, 2019)
Background: Atopic dermatitis (AD) is a chronic skin disease that affects 5-20% of children. This disease compromises the quality of life. Omalizumab offers a promising role in the treatment of severe atopic dermatitis.Objective: To share our experience with the use of omalizumab for treating severe AD in children.Methods: A retrospective review of the cases of pediatric patients with severe atopic dermatitis who were treated with omalizumab as an adjuvant therapy in an outside allergy service. Patients under 18 who had been treated for at least 6 months were included.Results: 19 patients were included. At the beginning of the study, all patients reported a compromise of life quality of 8/10 or more on a analogue scale. A majority of patients had previously received either systemic steroids or other immunosuppressive therapies without obtaining symptom control. At maximum treatment time, the obtained SCORAD scores revealed that the disease in 85.7% of the patients was mild/moderate while, in 14% of the patients, the disease was severe. The Children’s Dermatological Life Quality Index (CDLQI) was consistent with the SCORAD scores. From the beginning of treatment to the last visit to the doctor’s office, no patient required systemic steroid therapy.Conclusions: Omalizumab appears promising for treating severe atopic dermatitis in pediatric patients. That results shows that omalizubam improves the quality of life, also decreases the severity of the disease and the need for systemic steroid and immunosuppressive therapy, which decreases the side effects that are caused by these medications.